A four-generation family transmission chain of COVID-19 along the China–Myanmar border in October to November 2021 - Yan, Xiangyu; Xiao, Wei; Zhou, Saipeng; Wang, Xuechun; Wang, ZeKun; Zhao, Mingchen; Li, Tao; Jia, Zhongwei; Zhang, Bo; Shui, Tiejun (Frontiers in Public Health, 2022)
Background: Foreign imported patients and within-household transmission have been the focus and difficulty of COVID-19 prevention and control, which has also posed challenges to border areas’ management. However, household transmission caused by foreign imported cases has not been reported in China’s border areas. This study aimed to reveal a clear family clustering transmission chain of COVID-19 caused by contacts with Myanmar refugees along China-Myanmar border during an outbreak in October, 2021. Methods: During the outbreak, detailed epidemiological investigations were conducted on confirmed COVID-19 patients and their close contacts in daily activities. Patients were immediately transported to a designated hospital for treatment and quarantine, and their close contacts were quarantined at designated sites. Regular nucleic acid testing and SARS-CoV-2 antibody testing were provided to them. Results: A clear four-generation family clustering transmission involving five COVID-19 patients was found along the China-Myanmar border. The index case (Patient A) was infected by brief conversations with Myanmar refugees across border fences during work. His wife (Patient B) and nine-month-old daughter (Patient C) were second-generation cases infected by daily contact with him. His two-year-old daughter (Patient D) was the third-generation case infected by her mother and sister during quarantined in the same room, and then transmitted virus to her grandmother (Patient E, the fourth-generation case) who looked after her after Patient B and C were diagnosed and transported to hospital. Household secondary attack rate was 80.0%, average latent period was 4.0 days and generation time was 3.0 days. The household secondary attack rate was 80.0%, the average latent period was 4.0 days, and the generation time was 3.0 days. Ten of 942 close contacts (1.1%) of this family had positive IgM antibody during medical observation period. 73.9% (696/942) of them were positive for IgG antibody, and 8.3% (58/696) had IgG levels over 20 S/CO (optical density of the sample/cut off value of the reagent). Conclusion: This typical transmission chain indicated that it is essential to strengthen COVID-19 prevention and control in border areas, and explore more effective children care approaches in quarantine sites.